Analysis of student decision factors in choosing a study program - Basri, Irma Yulia; Giatman, Mohammad; Syah, Nurhasan; Elfina, Eni (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2024)
Education is one of the efforts taken by someone in realizing the career they plan. Errors in choosing a study program cause someone not interested in learning. The choice of study program by students is influenced by several factors, namely interests, family, finances, self-capacity, career opportunities, culture and colleagues. This study discusses the dominant factors that influence the selection of study programs for students of the Faculty of Engineering, Padang State University. The research respondents consisted of 262 students of the Faculty of Engineering, Padang State University (FT UNP). This type of research is qualitative research by describing the results of a questionnaire that has been filled out by respondents. The results showed that the two dominant factors that determined the choice of study program for FT UNP students were interest (88.9%) and career opportunities 89.1%. Meanwhile, the factors that contribute the least to the selection of study programs for students are family (46.1%) and surrounding culture (59.8%).